Cadmium (Cd) and lead (Pb) levels of Mediterranean mussel (Mytilus galloprovincialis Lamarck, 1819) from Bosphorus, Istanbul, Turkey - KAYHAN, FİGEN ESİN; GÜLSOY, NAGİHAN (Asian Network for Scientific Information, 2007)
In this study, bioaccumulation of cadmium (Cd) and lead (Pb) in Mediterranean mussels (Mytilus galloprovincialis Lamarck, 1819) at Bosphorus, Istanbul, Turkey, has been researched. Mussel samples hand-collected seasonally, between January, 2003 and December, 2004 from six stations in Bosphorus. The concentrations of Cd and Pb in the mussels were determinated by Atomic Absorption Spectrometry (AAS). The results of this study indicated that Cd and Pb were in higher concentrations in the Mussels of Bosphorus. The concentrations of these metals in soft tissues exceeded the acceptable levels for a food source for human consumption and these values are unacceptable for Turkish legal standards. © 2007 Asian Network for Scientific Information.
Keywords: Bosphorus; Cadmium; Lead; Marine pollution; Mytilus galloprovincialis